CONTINUING EDUCATION OF TEACHERS TEACHING MATHEMATICS IN THE CONTEXT OF LESSON STUDY: DISCUSSING LEARNING - Camacho Bezerra, Renata [UNESP]; Morellatti, Maria Raquel Miotto [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2023)
A Lesson Study corresponds to a formative process for teachers, which seeks to lead them to reflect on their practice, through collaborative and reflective work, focusing on student learning. In this text we present the results of an investigation carried out with a group of teachers who teach Mathematics in the early years of Elementary School whose guiding principle was: “How does Lesson Study contribute to the professional development of the teacher?”. This is a qualitative investigation of an interpretive nature and the data produced were collected through audio and video recording, narratives, participant observation and a questionnaire. As a result, we can infer that Lesson Study contributed to the teacher´s professional development, triggering learning processes of mathematical and didactic concepts, connections between theory and practice, reflections on the teaching and learning process, as well as changes in teacher practice and planning.
A FORMAÇÃO CONTINUADA DOS PROFESSORES QUE ENSINAM MATEMÁTICA NO CONTEXTO DA LESSON STUDY: DISCUTINDO AS APRENDIZAGENS
Keywords: Formation; Learning; Mathematics; Professional Development